Rola prasy dziecięcej w kształtowaniu kompetencji literackiej najmłodszych czytelników w dobie porozbiorowej = The role of the press in shaping literary competence of the youngest readers in the post-partition period - Uździcka, Marzanna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The aim of the text is to analyse the shaping of the press youngest readers? literary competence in the era of partitions, which was especially difficult for educational institutions. Periodicals for children at that time not only developed patriotic feeling and attitudes towards the nations and a state, which lost its sovereignty. Due to the dramatic situation of education and progressive russification and germanization, the press took an active part in education and constituted a teaching aid for popular then home schooling.
Keywords: doba porozbiorowa; prasa; prasa dziecięca; kompetencja literacka; twórczość dla dzieci; 19 w.; the post-partition period; 19th century children`s press; literary competence; creation for children